Transforming Legal Narratives: Postmodernism in South Asian English Literature - Nida Masroor; Mehwish Aslam; Dr Syeda Kaneez Fatima (Syntax Corporation Indonesia, 2023)
This study examines the relationship between law, literature, and postmodernism within the context of South Asian English literature. The objective of this study is to analyse the historical development of legal narratives and their subsequent influence on notions of human rights, cultural identity, and justice. Examining and challenging legal narratives,